Physical and chemical properties of aerosol particles and cloud residuals on Mt. Åreskutan in Central Sweden during summer 2014. Issue 1 (1st January 2020) - Graham, Emelie Linnéa; Zieger, Paul; Mohr, Claudia; Wideqvist, Ulla; Hennig, Tabea; Ekman, Annica M. L.; Krejci, Radovan; Ström, Johan; Riipinen, Ilona
Abstract: The size distribution, volatility and hygroscopicity of ambient aerosols and cloud residuals were measured with a differential mobility particle sizer (DMPS) and a volatility–hygroscopicity tandem differential mobility analyser (VHTDMA) coupled to a counterflow virtual impactor (CVI) inlet during the Cloud and Aerosol Experiment at Åre (CAEsAR) campaign at Mt. Åreskutan during summer 2014. The chemical composition of particulate matter (PM) and cloud water were analysed offline using thermo-optical OC/EC analysis and ion chromatography. The importance of aerosol particle size for cloud droplet activation and subsequent particle scavenging was clearly visible in the measured size distributions. Cloud residuals were shifted towards larger sizes compared to ambient aerosol, and the cloud events were followed by a size distribution dominated by smaller particles. Organics dominated both PM (62% organic mass fraction) and cloud water (63% organic mass fraction) composition. The volatility and hygroscopicity of the ambient aerosols were representative of homogeneous aged aerosol with contributions from biogenic secondary organics, with median volume fraction remaining (VFR) of 0.04–0.05, and median hygroscopicity parameter κ of 0.16–0.24 for 100–300 nm particles. The corresponding VFR and κ for the cloud residuals were 0.03–0.04 and 0.18–0.20. The chemical composition, hygroscopicity and volatility measurements thus showed no major differences between the ambient aerosol particles and cloud residuals. The VFR and κ values predicted based on the chemical composition measurements agreed well with the VHTDMA measurements, indicating the bulk chemical composition to be a reasonable approximation throughout the size distribution. There were indications, however, of some more subtle changes in time scales not achievable by the offline chemical analysis applied here. Further, online observations of aerosol and cloud residual chemical composition are therefore warranted.